2018
DOI: 10.4028/www.scientific.net/msf.929.186
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Carboxymethyl Cellulose-Oleic Acid Solid Biopolymer Electrolyte

Abstract: In this paper, the mechanical properties of carboxymethyl cellulose-oleic acid (CMC-OA) solid bio-polymer electrolyte (SBE) were examined. The host, CMC was doped with different weight percentage (wt. %) of OA in the CMC-OA solution. The SBEs were tested by using the Universal Material Testing Machine where the readings of tensile strength and Young’s modulus can be obtained from the stress-strain curve produced by the software during the tension test. The sample of CMC doped with 20% wt. of OA was found to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The changes physical structure of SPE films corresponding with the number of salts added will also have potential to alter the morphology respectively [30]. Besides, Ahmad and his team also reported that the addition of salt may influence the surface morphology of the films to make it become more flexible [31].…”
Section: The Physical Images Of Selected Spe Thin Filmsmentioning
confidence: 99%
“…The changes physical structure of SPE films corresponding with the number of salts added will also have potential to alter the morphology respectively [30]. Besides, Ahmad and his team also reported that the addition of salt may influence the surface morphology of the films to make it become more flexible [31].…”
Section: The Physical Images Of Selected Spe Thin Filmsmentioning
confidence: 99%